Robotic sample changers for macromolecular X‐ray crystallography and biological small‐angle X‐ray scattering at the National Synchrotron Light Source II. (23rd August 2021) - Lazo, Edwin O.; Antonelli, Stephen; Aishima, Jun; Bernstein, Herbert J.; Bhogadi, Dileep; Fuchs, Martin R.; Guichard, Nicolas; McSweeney, Sean; Myers, Stuart; Qian, Kun; Schneider, Dieter; Shea-McCarthy, Grace; et al.
Abstract : Robotic sample changers for macromolecular crystallography and biological small‐angle X‐ray scattering are presented. Abstract : Here we present two robotic sample changers integrated into the experimental stations for the macromolecular crystallography (MX) beamlines AMX and FMX, and the biological small‐angle scattering (bioSAXS) beamline LiX. They enable fully automated unattended data collection and remote access to the beamlines. The system designs incorporate high‐throughput, versatility, high‐capacity, resource sharing and robustness. All systems are centered around a six‐axis industrial robotic arm coupled with a force torque sensor and in‐house end effectors (grippers). They have the same software architecture and the facility standard EPICS‐based BEAST alarm system. The MX system is compatible with SPINE bases and Unipucks. It comprises a liquid nitrogen dewar holding 384 samples (24 Unipucks) and a stay‐cold gripper, and utilizes machine vision software to track the sample during operations and to calculate the final mount position on the goniometer. The bioSAXS system has an in‐house engineered sample storage unit that can hold up to 360 samples (20 sample holders) which keeps samples at a user‐set temperature (277 K to 300 K). The MX systems were deployed in early 2017 and the bioSAXS system in early 2019.